ANALISIS KELAYAKAN USAHATANI PADI SEMI ORGANIK DAN NON ORGANIK DI KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - Wizatul Ika Wulandari; Tajidan Tajidan; Dudi Septiadi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2022)
This study aims to: (1) determine the income of semi-organic and non-organic rice farming systems in Pringgasela District, East Lombok Regency (2) analyze the feasibility of semi-organic and non-organic rice farming systems in Pringgasela District, East Lombok Regency. The results of the study show that: (1) There are differences in income in rice farming activities, where the income of farming using a semi-organic system is Rp. 20,446,865 per hectare; (2) The results of the R/C Ratio of semi-organic and non-organic rice have similarities, namely both are not feasible or inefficient because they are smaller than 1 (R/C Ratio < 1). This means that semi-organic and non-organic rice farming in Pringgasela District, East Lombok Regency is inefficient or unfit for cultivation.